STATE RESPONSIBILITY IN SAFEGUARDING WORKERS DISMISSED FROM EMPLOYMENT: A STUDY OF JOB LOSS INSURANCE (JKP) - Ansrida, Destin Desy; Efendi, Dr. Jonaedi (jfpublisher, 2025)
Employment termination (Pemutusan Hubungan Kerja/PHK) has become an increasingly common issue in Indonesia’s labor landscape. To address this, the government introduced the Job Loss Guarantee (Jaminan Kehilangan Pekerjaan/JKP) through Government Regulation in Lieu of Law Number 2 of 2022, later enacted as Law Number 6 of 2023 concerning Job Creation. The JKP program serves as a form of state protection aimed at supporting Indonesian workers affected by layoffs, offering structured benefits administered by BPJS Ketenagakerjaan. This research aims to examine the legal basis of the JKP program as a new social protection policy and to evaluate the legal protection mechanisms available for terminated workers in accessing these benefits. Using a normative juridical approach, the study analyzes relevant laws, regulations, and institutional responsibilities, supported by academic sources and policy documents. The research also seeks to identify potential legal uncertainties, regulatory weaknesses, and institutional barriers that may hinder the effective implementation of JKP. The findings are expected to provide legal insight and contribute to the development of more responsive employment-based social security policies in Indonesia.